1988
DOI: 10.1002/chin.198828153
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Structure of an Amine‐Stabilized Sulfene, RHC=SO2·N(CH2CH2)3CH.

Abstract: ChemInform Abstract The synthesis of the title compound (III) can be accomplished by the reaction of mesyl chloride (I) with quinuclidine (II). The structure of (III) is determined by X-ray analysis ( P21/n; Z=4). Treatment of (III) with H2O/MeCN yields the expected salt (IV) which can be independently obtained by reaction of disulfene (V) and quinuclidine (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…The quinuclidine cage in 1 is twisted and the average N−C−C−C dihedral angle is 8.4°. This is consistent with the reported intracage twist angle observed in the solid-state structure for complexes of parent quinuclidine with osmium (8.8°) and sulfimide (7.7°), but 3° is a more typical value for this angle. The average C−N bond length of 1.524 Å and the C···N interbridgehead distance of 2.637 Å observed in 1 are longer than typical values of about 1.50 and 2.56 Å found in other quinuclidine derivatives 27-31 but are consistent with the C−N distance and interbridgehead separation found in a quinuclidine−CBr 4 complex (1.525 and 2.626 Å, respectively) …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The quinuclidine cage in 1 is twisted and the average N−C−C−C dihedral angle is 8.4°. This is consistent with the reported intracage twist angle observed in the solid-state structure for complexes of parent quinuclidine with osmium (8.8°) and sulfimide (7.7°), but 3° is a more typical value for this angle. The average C−N bond length of 1.524 Å and the C···N interbridgehead distance of 2.637 Å observed in 1 are longer than typical values of about 1.50 and 2.56 Å found in other quinuclidine derivatives 27-31 but are consistent with the C−N distance and interbridgehead separation found in a quinuclidine−CBr 4 complex (1.525 and 2.626 Å, respectively) …”
Section: Resultssupporting
confidence: 88%
“…This is consistent with the reported intracage twist angle observed in the solid-state structure for complexes of parent quinuclidine with osmium (8.8°) 26 and sulfimide (7.7°), 27 but 3°is a more typical value for this angle. [28][29][30][31] The average C-N bond length of 1.524 Å and the C‚‚‚N interbridgehead distance of 2.637 Å observed in 1 are longer than typical values of about 1.50 and 2.56 Å found in other quinuclidine derivatives [27][28][29][30][31] but are consistent with the C-N distance and interbridgehead separation found in a quinuclidine-CBr 4 complex (1.525 and 2.626 Å, respectively). 32 The quinuclidine forms a 5°dihedral angle with the cage and its orientation is closer to the idealized eclipsed rather than the staggered conformation (Figure 3) characteristic for the CB 11 H 11 -1-NMe 3 analogue.…”
Section: Resultssupporting
confidence: 73%
“…[6] Its characterization was based solely on an elemental analysis, no further spectroscopic or structural information (NMR, IR, UV/Vis, MS, or X-ray) being given. Adducts of electron acceptor-substituted sulfenes with Lewis bases stronger than pyridine, such as the adducts of mesylsulfene with trimethylamine [7] or quinuclidine [8] and the bis(trifluoromethyl)sulfeneϪ quinuclidine adduct, [9,10] have been characterized by NMR and X-ray crystallography. In the case of the quinuclidineϪmesylsulfene and quinuclidineϪbis(trifluoromethyl)sulfene adducts, X-ray crystallography [8Ϫ10] revealed that the tertiary amines were bound through SϪN bonds.…”
Section: Introductionmentioning
confidence: 99%